Radiation Technology for control of Listeria monocytogenes and Yersinia enterocolitica in Fish - Kamat, Anu; Bongirwar, Dilip (Fishery Technology, 2025)
The efficacy of the radicidation as a method of preservation of fish was evaluated by artificially inoculating Listeria monocytogenes or Yersinia enterocolitica cells prior to irradiation and detecting the respective pathogen during storage at 2-40C. These studies when repeated with two serotypes of L monocytogenes clearly suggested the need of a dose of 3 kGy for elimination of 103 cfu.g"1 from air packed frozen shrimp. In case of Y. enterocolitica, a dose of 1 kGy was sufficient to eliminate naturally occurring low numbers from shrimp without any revival during storage at chilled temperature for two weeks. The initial level of contamination was an important factor in deciding the dose of radiation for effective control of growth of these organisms.